Towards Optimal Taxes: Impact of Tax Extensification and Intensification on Individual Income Tax Receipts - Pasolo, Muhammad Ridhwansyah; Ermawati, Yana; Sonjaya, Yaya; Sumartono, Sumartono (Advances in Taxation Research, 2023)
Purpose: This study examines the impact of tax extensification and intensification on individual income tax receipts, determining whether expanding the taxpayer base and improving compliance significantly contribute to revenue growth. Research Design and Methodology: A quantitative approach using multiple linear regression analysis was applied to assess the relationship between tax extensification, tax intensification, and individual income tax receipts. Primary data were collected from 100 registered taxpayers at KPP Pratama Jayapura through a structured questionnaire-based survey. Statistical tests include validity, reliability, normality, heteroscedasticity, multicollinearity, and hypothesis testing, including the coefficient of determination, t-test, and F-test. Findings and Discussion: The results indicate that tax extensification and intensification significantly enhance tax revenue. Expanding the taxpayer base and improving compliance monitoring contribute to increased revenue collection, aligning with attribution theory and highlighting internal (awareness, responsibility) and external (regulatory frameworks, enforcement) compliance factors. Implications: This study highlights the need for more substantial tax administration, digital infrastructure, and taxpayer education. Governments should enhance compliance monitoring and enforcement to sustain revenue growth. Future research should explore additional compliance factors, such as penalties and digital tax services.